Letter from Roger Casement to Francis H. Cowper about how he is not returning to the Congo: "the Congo State wouldn't have me! My report has finished me there" - Casement, Roger, 1864-1916; Cowper, Francis H. (1904)
Casement hopes that his dog, "John", is well.
Manuscript in black ink on plain paper, addressed from: "c/o H.S. King & Co / 9 Pall Mall, / London". Envelope addressed to: "Francis H. Cowper Esq, / H.B.M. Consul / Consulado Britannico, / Lisbon / Portugal".
Keywords: Casement, Roger, -- 1864-1916 -- Correspondence; Cowper, Francis H. -- Correspondence; Diplomatic and consular service, British; Human rights workers; Irish -- Africa -- 20th century